Petrogenesis of early–middle paleozoic granitoids in the qilianblock, northwest China: Insight into the transition from adakitic to non-adakitic magmatism in a post-collisional extensional setting - Zhao, Jiao-Long; Chen, Wan-Feng; Wang, Jin-Rong; Tang, Qing-Yan; Wang, Er-Teng; Fu, Yi-Qiao (Frontiers in Earth Science, 2022)
To better understand geodynamic implications for the transition from adakitic to non-adakitic magmatism in a continental collision setting, an integrated study including zircon U–Pb ages and whole-rock geochemistry was performed for the Gahai and Erhai granitoid intrusions within the Qilian Block. The ca. 450–428 Ma Gahai biotite granite and Erhai muscovite-bearing granite are peraluminous S-type granites with adakitic geochemical characteristics, and have low Mg# (41.2–31.7) and εNd(t) (-10.8– -6.5) values with two–stage Nd model ages of 2.05–1.72 Ga, implying their derivation almost entirely from an ancient crustal source under a thickened lower crust condition. The geochemical characteristics of the granites indicate that the Gahai and Erhai S-type granites were derived from partial melting of meta-greywacke and meta-pelite sources, respectively. In comparison, the ca. 415 Ma Gahai granodiorite belongs to metaluminous I-type granitoid and has low Sr/Y ratios as well as high Y and heavy rare earth element (REE) concentrations, with nearly flat heavy REE patterns, implying a shallow source region. The granodiorites were most likely generated by partial melting of a K-rich basaltic magma source, with some contributions from mantle-derived melts. Synthesized data from this and previous studies suggest that the ca. 450–415 Ma Gahai and Erhai granitoids within the Qilian Block were generated in a post-collisional extensional regime triggered by the break-off of the northward subducting South Qilian Ocean slab beneath the Qilian Block. The geochemical transition from adakitic to non-adakitic intermediate-acidic magmas indicated that the thickened continental crust of the Qilian Block had experienced significant extension and thinning after ca. 420 Ma.